Investigation on four‐port mono‐capacitor circuit with high‐pass negative group delay behavior. (8th November 2021) - Fenni, Sofia; Haddad, Fayrouz; Jaomiary, Antonio; Yazdani, Samar S.; Sahoa, Frank Elliot; Ramifidisoa, Lucius; Guerin, Mathieu; Rahajandraibe, Wenceslas; Ravelo, Blaise
Abstract: Most of the recent studies on unfamiliar negative group delay (NGD) circuit were focused on the classes of low‐pass (LP) and bandpass (BP) topologies. So far, few research works are currently available in the literature on the high‐pass (HP) NGD class. This paper introduces an original HP‐NGD circuit theory of four‐port passive topology constituted by a single lumped capacitor. The S‐matrix equivalent model of the innovative topology is established from the admittance matrix. The basic analytical frequency‐dependent responses are expressed. Then, the GD model is derived in function of the capacitor. It was analytically found that the four‐port mono‐capacitor passive circuit is susceptible to behave as an unfamiliar class of HP‐NGD function. An innovative HP‐NGD analysis is explored in addition to the expression of synthesis design equation in function of the expected NGD cut‐off frequency which is linked to NGD optimal value. The validity of the established HP‐NGD theory is verified with a proof of concept (POC) circuit. As expected, the POC enables HP‐NGD behavior to show a good correlation between analytical model which is confirmed by the simulation. Abstract : This paper investigates on original high‐pass (HP) NGD mono‐capacitor circuit. The main specifications of the unfamiliar HP‐NGD function are defined. The S‐parameter equivalent model of the mono‐capacitor four‐port cell is developed. The well‐correlated theoretical and simulation validations of the HP‐NGD behavior from mono‐capacitor circuit proof‐of‐concept are discussed.